2008
DOI: 10.1126/science.1160619
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Antibiotics Control Gene Expression and Community Behavior in Divergent Bacteria

Abstract: It is thought that bacteria excrete redox-active pigments as antibiotics to inhibit competitors. In Pseudomonas aeruginosa, the endogenous antibiotic pyocyanin activates SoxR, a transcription factor conserved in Proteo- and Actinobacteria. In Escherichia coli, SoxR regulates the superoxide stress response. Bioinformatic analysis coupled with gene expression studies in P. aeruginosa and Streptomyces coelicolor revealed that the majority of SoxR regulons in bacteria lack the genes required for stress responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
392
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(410 citation statements)
references
References 31 publications
16
392
2
Order By: Relevance
“…Indeed, owing to the high pH (7.9) and CaCO 3 content of the Châteaurenard soil, the concentration of extractable iron was shown to be 15 times lower than that in the Carquefou soil (Lemanceau et al, 1988). As phenazines are redox-active antibiotics (Dietrich et al, 2008) and may contribute to iron mobilization in soils (Hernandez et al, 2004;Price-Whelan et al, 2006;Wang and Newman, 2008), the ability of bacteria to produce these metabolites may give them a competitive advantage under the iron-limiting conditions prevailing in the Châteaurenard suppressive soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, owing to the high pH (7.9) and CaCO 3 content of the Châteaurenard soil, the concentration of extractable iron was shown to be 15 times lower than that in the Carquefou soil (Lemanceau et al, 1988). As phenazines are redox-active antibiotics (Dietrich et al, 2008) and may contribute to iron mobilization in soils (Hernandez et al, 2004;Price-Whelan et al, 2006;Wang and Newman, 2008), the ability of bacteria to produce these metabolites may give them a competitive advantage under the iron-limiting conditions prevailing in the Châteaurenard suppressive soil.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the additional suppression provided by the bacterial and fungal combination was ascribed earlier to an interplay between carbon and iron competition achieved by these two groups of antagonistic microorganisms (Lemanceau et al, 1988: pyoverdine-mediated iron competition achieved by the fluorescent pseudomonads was shown to reduce the efficacy of carbon metabolism of the pathogenic F. oxysporum making it more susceptible to carbon competition with non-pathogenic F. oxysporum . Considering that phenazines are redox-active antibiotics (Dietrich et al, 2008) and may contribute to iron mobilization in soils (Hernandez et al, 2004;Price-Whelan et al, 2006), they also could play a role in iron competition, thereby making pathogenic F. oxysporum more susceptible to carbon competition with non-pathogenic F. oxysporum. Alternatively, phenazines also could act against pathogenic F. oxysporum as redox-active antibiotics leading to the accumulation of toxic oxygen radicals .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pyocyanin was shown to have a function in signalling, responsible for the upregulation of specific genes, such as the genes involved in ferric iron acquisition and of the operon encoding the efflux pump MexGHI-OpmD PriceWhelan et al, 2006). Recently, it was shown that phenazine-defective mutants produce wrinkled colonies and accumulate NADH in the cells (Dietrich et al, 2008;Price-Whelan et al, 2007;Wangt & Newman, 2008). Pyocyanin is the phenazine that interacts most strongly with oxygen (Wangt & Newman, 2008) and it was proposed by Price-Whelan et al (2007) that externally added pyocyanin could give electrons to molecular oxygen to reduce it to water by oxidizing internal NADH to NAD.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa, along with a variety of other bacteria, produce redox-cycling antibiotics called phenazines (29,41). In susceptible bacteria such as E. coli, phenazines enter the cell and produce superoxide by oxidizing cytoplasmic targets and reducing molecular oxygen (42).…”
Section: Curliated Bacteria Are Localized To the Air-biofilm Interfacmentioning
confidence: 99%
“…Along with curli, cellulose aids cell-to-cell attachment and adherence to inorganic surfaces and host cells (24)(25)(26). UTI89 and a variety of other bacterial species form rugose biofilms (also known as rdar) on agar plates (4,23,(27)(28)(29). In both S. typhimurium and E. coli, the CsgD-regulated matrix components curli and cellulose are necessary for development of rugose biofilms (23,27,30).…”
mentioning
confidence: 99%